DEMANDA DE MÃO DE OBRA DA PETROBRAS POR NÍVEIS DE COMPETÊNCIAS A PARTIR DA DESCOBERTA DO PRÉ-SAL - Pinto, Gilson Mendes (2014)
The main objective of the research is seeking lifting, analyze, quantify and sort by levels of competences which professionals were recruited by Petrobras after the discovery of the Brazilian subsalt layer. The research is justified by the expected growth in domestic production of oil and natural gas estimated for the coming years which may cause an imbalance between supply and demand of manpower for their development. The methodological approach developed for conducting the research was an exploratory, descriptive documentary research through qualitative and quantitative longitudinal analysis. As a first result the research has revealed that Petrobras does not use to recruit professionals for positions at managerial positions. The results also demonstrated that 56.8pc of the open recruitment vacancies are for professionals with middle level degree and 76.4pc of the vacancies are related to the manufacturing process showing that Petrobras uses as a gateway to hire professionals with middle level degree with technical training qualification. When performing classification and qualification of job opportunities opened to recruitment the research identified five groups of professionals spread along three carrers aisle and four salarial levels that when classified by career and categorized by levels of competences were responsible for 69% of job opportunities opened to recruitment. The two first relevant groups has career related to industrial operations where the upper level (O6) and the lower level (O1) were responsible for 22pc and 21pc respectively of the total number of job opportunities offered in the period. The third group in importance has career related to engineering, processes and projects which is categorized as medium level (E3) on a scale between two and five and these professionals were responsible for 13pc of total number of job opportunities offered. The fourth and fifth groups has career related to business management and when categorized by levels of competences at third (G3) and fourth levels (G4) on a scale between one and five these professionals are responsible for 7pc and 6pc of job opportunities opened to recruitment.